ON POINTS OF VIEW, PERSPECTIVES, FRAMES, SCENARIOS AND SCHEMAS. DOES NON-CONCEPTUALITY PLAY A RELEVANT ROLE? ON POINTS OF VIEW, PERSPECTIVES, FRAMES, SCENARIOS AND SCHEMAS. DOES NON-CONCEPTUALITY PLAY A RELEVANT ROLE? - Brugnami, Enrico (Analysis. Journal of Philosophical Research, 2024)
This article explores the role of non-conceptuality in perspectives, points of view, frames, scenarios and schema. It argues for the hybrid nature of perspectives, frames and schemas. Against the idea that the concepts mentioned are purely conceptual or that their most important characteristic is conceptual, the article emphasizes the fundamental role of non-conceptual content. In the case of frames, we compare them with the notion of schema as used in psychology and cognitive behavioural therapy, illustrating how non-conceptual frames influence perception, decision-making, and courses of action. The analysis proposes a understanding of these concepts as interrelated and argue that the non-conceptual aspects of frames and schemas affect drastically the points of view we hold and the scenarios we imagine.